Stellar models of rotating, pre-main sequence low-mass stars with magnetic fields. Issue Volume 9:Issue S302(2013) (7th August 2014) - Mendes, Luiz T. S.; Landin, Natália R.; Vaz, Luiz P. R.
Abstract: We report our present efforts for introducing magnetic fields in theATON stellar evolution code code, which now evolved to truly modifying the stellar structure equations so that they can incorporate the effects of an imposed, large-scale magnetic field. Preliminary results of such an approach, as applied to low-mass stellar models, are presented and discussed.